Policy on the use of Machine Translation (MT): A good model for wider policies on Generative AI (GenAI)? - Cotelli Kureth, Sara; Elana Summers (My University, 2025)
Since the advent of ChatGPT and other automatic text generators, educators from many disciplines, including language learning and teaching, have published numerous articles exploring this technology’s “pitfalls and potentials” (Barrot, 2023) and offering recommendations based on their own practice to teachers, users, and institutional decision-makers. But it is early days yet, and, while recognising the need to offer guidance, there is not enough scientific data to create evidence-based policies. Having been working on machine translation (MT) literacy (Bowker & Buitrago Ciro, 2019; Cotelli Kureth & Summers, 2023) for several years, we have developed guidelines for the use of machine translation (MT) tools in higher education, which have been implemented in a Swiss university. Given that MT tools share technical features with generative AI (GenAI) tools like ChatGPT, we believe that applied knowledge of the former could facilitate understanding of the latter. This article will draw on both our own experience and a thorough literature review of recommendations for the use of GenAI for higher education institutions (HEI) to map what guidelines on the use of GenAI should include and how they should be presented to teachers and users.
Keywords: Generative AI; guidelines; higher education institutions; machine translation; policies